Management of oxaliplatin-induced peripheral neuropathy - Saif, M Wasif (Dove Medical Press, 2005)
Neurotoxicity is the most frequent dose-limiting toxicity of oxaliplatin. Acute sensory neurotoxicity manifests as rapid onset of cold-induced distal dysesthesia and/or paresthesia, sometimes accompanied by cold-dependent muscular contractions of the extremities or the jaw. The symptoms, often occurring during or shortly after infusion, are usually transient and mild. A cumulative sensory peripheral neuropathy may also develop with prolonged treatment with oxaliplatin, eventually causing superficial and deep sensory loss, sensory ataxia, and functional impairment. Studies have shown patients with acute sensory symptoms to display little or no axonal degeneration. The similarity of acute symptoms induced by oxaliplatin to those caused by several drugs or toxins acting on neuronal or muscular ion channels suggests that these symptoms may result from a specific interaction of oxaliplatin with voltage-gated sodium (Na(+)) channels. The current recommendations for the management of the acute and cumulative neurotoxicity from oxaliplatin include education about exposure to cold, dose modification, “stop and go”, and use of neuromodulatory agents, in particular, intravenous calcium and magnesium infusion. Upon the approval of oxaliplatin-based regimens both for adjuvant and metastatic treatment of colon cancer, it is crucial to compile knowledge about the recognition and management of neurotoxicity from oxaliplatin.